Safety of third dose of COVID-19 vaccination in frail patients: Results from the prospective Italian VAX4FRAIL study - Di Cosimo, Serena; Lupo-Stanghellini, Maria Teresa; Costantini, Massimo; Mantegazza, Renato; Ciceri, Fabio; Salvarani, Carlo; Zinzani, Pier Luigi; Mantovani, Alberto; Ciliberto, Gennaro; Uccelli, Antonio; Baldanti, Fausto; Apolone, Giovanni; et al. (Frontiers in Oncology, 2022)
Abstract Importance: Despite people with impaired immune competence due to an underlying disease or ongoing therapy, hereinafter frail patients, are (likely to be) the first to be vaccinated, they were usually excluded from clinical trials. Objective: To report adverse reactions of frail patients after receipt of the third dose (booster) administered after completion of a two-dose mRNA vaccination and to compare with those reported after receipt of the second dose. Design: A multicenter, observational, prospective study aimed at evaluating both the safety profile and the immune response of Pfizer-BioNTech or Moderna vaccination in frail patients. Setting: National Project on Vaccines, COVID-19 and Frail Patients (VAX4FRAIL) Participants: People consenting and included in the VAX4FRAIL trial Exposure A series of three doses of COVID-19 mRNA vaccination from the same manufacturer Main Outcome(s) and Measure(s): Self-reported adverse events Results: Among 320 VAX4FRAIL participants diagnosed/treated for hematological malignancies (N=105; 32.8%), solid tumors (N=48; 15.0%), immune-rheumatological diseases (N=60; 18.8%), neurological diseases (N=107; 33.4%), and receiving the booster dose, 70.3% reported at least one loco-regional or systemic reactions. Adverse events were mostly mild or moderate, none being life-threatening. Only six of the 320 (1.9%) patients had their treatment (postponed) due to the vaccine. The safety profile of the booster compared to previously administered two doses showed shows a stable prevalence of patients with one or more adverse events (73.5%, 79.7% and 73.9% respectively), and a slightly increment of patients with one or more severe adverse events (13.4%, 13.9% and 19.2% respectively) Conclusions and Relevance: The booster of the mRNA COVID-19 vaccine was safely administered in the largest prospective cohort of frail patients reported so far. VAX4FRAIL will continue to monitor the safety of additional vaccine doses, especially systemic adverse events that can be easily prevented to avoid interruption of continuity of care. Trial Registration: NCT04848493